From old to modern socio-cultural transformation in Oman in the novel of Sayyidātul Qomar by Jukhah Al-Hāriṡy - Laluhun, Putri (Association for Scientific Computing Electrical and Engineering (ASCEE), 2024)
This study aims to describe the aspects of socio-cultural transformation from old to modern and to explain the process of socio-cultural change in Oman through Sayyidātul Qomar's novel by using a socio-cultural approach and socio-cultural theory by Koentjaningrat. The object of this research is the novel Sayyidātul Qomar by Jukhah Al-ḥāriṡy, which was published by the publisher Dār al-Ādāb in 2010 in Beirut, Lebanon. The method used in this research is a descriptive qualitative method using data collection techniques in the form of a literature study. The results showed that the aspects of socio-cultural transformation that occurred in Oman in the novel were the religious/belief system, society, education/knowledge, economy, government and technology, and life equipment. The process of socio-cultural transformation from old to modern is divided into two, namely, the driving factors for the transformation and the problems/conflicts in the transformation process. These driving factors include political factors (changes in the power system), economic crises (trade crises), feminism (women's struggles for their rights as women), and open society systems (birth of new generations). These problems/conflicts include the conflict between science and the supernatural, the rebels and the Omani government, the human world and the Jinn, and the enslaver and enslaved person.